2016
DOI: 10.1080/15374416.2016.1204921
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Moderates the Association Between Response Inhibition and Self-Regulation in Early Childhood

Abstract: Early childhood is a time of rapid developmental changes in sleep, cognitive control processes, and the regulation of emotion and behavior. This experimental study examined sleep-dependent effects on response inhibition and self-regulation, as well as whether acute sleep restriction moderated the association between these processes. Preschool children (N = 19; 45.6 ± 2.2 months; 11 female) followed a strict sleep schedule for at least 3 days before each of 2 morning behavior assessments: baseline (habitual nap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 113 publications
(159 reference statements)
0
30
0
Order By: Relevance
“…Further, this study is focused on children from low‐income families, who are at relatively high risk for both self‐regulation and sleep difficulties. As suggested by prior work (Chiang et al., ; Schumacher et al., ; Tu, Erath, & El‐Sheikh, ) which is informed by the differential susceptibility model (Ellis et al., ), we hypothesize that toddler sleep will moderate the association between parenting and toddler self‐regulation such that toddlers who obtain less nighttime sleep and are exposed to negative parenting will have poorer self‐regulation skills than will those who obtain more sleep. We also examined effects of positive parenting and demographic covariates in an exploratory manner.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Further, this study is focused on children from low‐income families, who are at relatively high risk for both self‐regulation and sleep difficulties. As suggested by prior work (Chiang et al., ; Schumacher et al., ; Tu, Erath, & El‐Sheikh, ) which is informed by the differential susceptibility model (Ellis et al., ), we hypothesize that toddler sleep will moderate the association between parenting and toddler self‐regulation such that toddlers who obtain less nighttime sleep and are exposed to negative parenting will have poorer self‐regulation skills than will those who obtain more sleep. We also examined effects of positive parenting and demographic covariates in an exploratory manner.…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, associations between maternal sensitivity and later behavioral outcomes among infants are stronger in those who obtain more nighttime sleep than in those who sleep for shorter durations at night (Bordeleau, Bernier, & Carrier, ). Prior work also has shown that response inhibition is related to adaptive self‐regulation strategy use in preschool‐aged children, but this relationship disappeared when child sleep was restricted by about three hours (Schumacher et al., ). Poor integration of cognitive and emotional processes in this manner may place children at risk for future psychopathology (reviewed in Blair & Dennis, ), and children from low‐income families who are not getting adequate sleep may be particularly susceptible to later problems (El‐Sheikh, Kelly, Buckhalt, & Hinnant, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this special issue, Schumacher and colleagues (2017) examine the impact of 1 night of sleep restriction (keeping a child up 3 hr past regular bedtime) on response inhibition and self-regulation in healthy, typically developing preschoolers. Sleep restriction was found to moderate the relationship between response inhibition and adaptive self-regulation; specifically, a strong association was found when children were well rested but not when they were sleep deprived (Schumacher et al, 2017). Although examining only acute sleep restriction, this study begins to shed light on the role that sufficient sleep duration plays in the emotional development of young children.…”
Section: Mechanisms and Trajectoriesmentioning
confidence: 99%
“…A single night of significant sleep loss (3 hr) has been shown to negatively impact outcomes in preschoolers (Schumacher et al, 2016). But it is more common for youth to chronically experience small amount of sleep loss (e.g., 30-60 min) every night across the school week, especially if there is technology in the bedroom (Buxton et al, 2015;Mindell et al, 2009).…”
Section: Individual Vulnerability To Sleep Loss?mentioning
confidence: 99%